Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov. - Zhang, Hao-Miao; Guan, Zhao-Ying; Wang, Wen-Zhi (Zootaxa, 2017)
A new gomphid species, named as Gomphidictinus tongi sp. nov. (Holotype male, Mt. Diaoluoshan, altitude 930m a.s.l., Lingshui County, Hainan Province, China) is described here. It is regarded as the third species of Gomphidictinus based on the presence of the basal spine on median segment of the penis organ. Gomphidia interruptistria Zha, Zhang & Zheng, 2005 is regarded as a junior synonym of Gomphidictinus perakensis (Laidlaw, 1902), which is recorded from Yunnan, China.